1986
DOI: 10.3382/ps.0650757
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Broiler Chickens to the Addition of Bacitracin Methylene Disalicylate to Diets Containing Salinomycin and Roxarsone

Abstract: Two experiments were conducted to evaluate the response of broiler chickens to addition of bacitracin methylene disalicylate (BMD) to diets containing salinomycin. In each experiment, five tests were conducted at different locations. In Experiment 1, all diets contained 66 mg salinomycin/kg of diet for the first 42 days and either 0 or 33 mg BMD/kg of diet for the entire 49-day feeding period. In Experiment 2, all diets contained 66 mg salinomycin and 50 mg roxarsone/kg of diet for the first 42 days and either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 22 publications
(23 reference statements)
1
1
0
Order By: Relevance
“…Concurrently, prevalence of foodborne pathogens in the ceca and ilea was also investigated. Similar to earlier published reports [ 3 , 5 , 30 , 31 ], our study observed an increase in production performance response to dietary supplementation of bacitracin in the early phase (until d22) of chick growth. However, growth performance response to in-feed antibiotics was inconsistent across all ages [ 16 ] and reports indicate growth depression in broilers fed salinomycin [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Concurrently, prevalence of foodborne pathogens in the ceca and ilea was also investigated. Similar to earlier published reports [ 3 , 5 , 30 , 31 ], our study observed an increase in production performance response to dietary supplementation of bacitracin in the early phase (until d22) of chick growth. However, growth performance response to in-feed antibiotics was inconsistent across all ages [ 16 ] and reports indicate growth depression in broilers fed salinomycin [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…In North America, antibiotic growth promoters (AGPs), commonly used in the poultry industry include: Avilamycin, Enramycin, Monensin, Penicillin, Virginamycin and Bacitracin methylene disalicylate (BMD) [ 3 ]. BMD is commonly used in the broiler diet for the prevention and control of necrotic enteritis, as well as improvement of weight gain and feed efficiency [ 4 , 5 ]. Inclusion of antibiotics in poultry diet can also reduce the prevalence of enteric pathogens.…”
Section: Introductionmentioning
confidence: 99%